Peran Gereja Dalam Pemuridan di Era Masyarakat Postmodernisme - Stevie Kalangi (Institut Agama Kristen Negeri Palangka Raya, 2023)
Postmodernism is philosophy stream that emerged in late modern times, the core philosophy of postmodernism is the rejection of the basic assumptions and principles of modernism. Discussion of postmodernism is not something new, but has become a hot discussion among contemporary thinkers. The presence of postmodernism is a serious threat to Christian teaching. The concept of postmodern truth which is a resistance to modern truth has formulated a new view. Even though postmodernism has a different perspective from modernism, this does not mean that the views of postmodernism can be fully accepted. The view of postmodernism is a rejection of objective truth, rejection of absolute truth and rejection of universal truth. The purpose of writing this reach article is first, to explain the background and various concepts of postmodernism. Second, to explain the existence of the church in the form of its role and function as an agent of change in the postmodern era of society. The type of research used is a descriptive qualitative research of the literature with the steps of analyzing and synthesizing library data related to the existence of the church and the view of postmodernism. The benefit of this research is as material for study for students of theology study programs in the development of theology knowledge related to contemporary theological issues.